Искушение Ворона: роман / Д. Вересов - Вересов Дмитрий (Нева, 2004)
Экземпляры: Ф. 13 (20230307) / Инвентарный номер: 49761 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 31 / ББК: 84(2Рос=Рус)6